Feeding in syntopy: diet of Hydromedusa tectifera and Phrynops hilarii (Chelidae) - Alcalde, Leandro (2010)
Stomach contents were obtained from 25 Hydromedusa tectifera and 47 Phrynops hilarii that live in syntopy in a pampasic stream in Buenos Aires province, Argentina. Both species are arthropod consumers. Copepods, ostracods, and hemipterans are the preferred items for P. hilarii, and H. tectifera prefers copepods, ostracods, immature dipterans (mainly chironomids), and ephemeropteran larvae. Items that most contribute to the diet of both species are immature chironomids, corixids, and belostomatids. Available food varies little among seasons, being slightly lower in winter months and part of the summer. Diet diversity changes by seasonal variation of prey item abundance in the diet of both species. Diet diversity is higher for P. hilarii (more generalist and broader trophic niche) than in H. tectifera, but there is no niche overlap between them. No significant correlation between the size of turtles and length of prey items was found. There is no evidence that the long neck of H. tectifera relates to piscivorous habits, because fish are a small fraction of its diet and arthropods constitute the bulk of the ingested items.